Frequency, patterns of use, and perceptions about natural remedies among adults in the United Arab Emirates regarding COVID-19 - Razan Ibrahim Faris Yousef; Eman Mohamad El Khatib; Hashim Almishhadany; Amna Ibrahim Zaidan; Jennat Alamara; Mohammed Rahim Hossain; Hiba Jawdat Barqawi; Saryia Adra; Eman Abu Gharbieh (BMC Complementary Medicine and Therapies, 2026)
Abstract Introduction The global coronavirus disease (COVID-19) pandemic drove significant interest in alternative options for disease prevention and treatment. Among these alternatives, natural remedies (NRs) gained considerable attention. This study aims to explore the frequency, usage patterns and perceptions regarding NRs for the prevention and treatment of COVID-19 among adults in the United Arab Emirates (UAE). Methods A cross-sectional study was conducted between February and March 2021 using a self-administered questionnaire distributed through social media platforms. The study targeted UAE residents aged 18 and above. For the purpose of the study we defined adults in the UAE as individuals aged 18 and above. Collected data was analysed using SPSS version 26. Results A total of 382 responses were analyzed. Before the pandemic, 74.6% (n = 285) used NRs for disease prevention and/or treatment, but only 27.7% (n = 106) used them for COVID-19 prevention, 3.9% (n = 15) for treatment, and 11.8% (n = 45) for both. Sex (p = 0.011), and age (p = 0.045) were significantly associated with NR use against COVID-19. Most participants believed that NRs had low efficacy in preventing (41.6%, n = 159) or treating (52.9%, n = 202) COVID-19. Among those with a COVID-19 history, 42.9% (n = 24) believed NRs made quarantine unnecessary, compared to 25.6% (n = 79) without such a history. No significant difference in perceived risk was found between NR users and non-users. Conclusion The frequency of NR for COVID-19 prevention or treatement was very low in the UAE, as such community outreach and public health programs are needed to raise awareness about the potential role of natural remedies in supporting health and well-being.